Analysis of Industrial Design Rights Protection in Supreme Court of Indonesia Number 1865 K/PDT.SUS-HKI/2022 Based on The Principle of Novelty and The Principle of Good Faith in Law Number 31 of 2000 - Mardiana; Rahmadina, Adji Annisa; Asufie, Khairunnisa Noor (Ipso Jure, 2025)
This study examines the Analysis of Industrial Design Rights Protection in the Supreme Court Decision No. 1865 K/Pdt.Sus-HKI/2022 as mandated by Law No. 31 of 2000 concerning Industrial Designs. The main issue discussed is the application of the principles of novelty and good faith in the legal protection of industrial designs, as well as how the court applies these principles in its judgment. The purpose of this research is to analyze the urgency of applying the principles of novelty and good faith to maintain a balance between the exclusive rights of design owners and the public interest, and to assess the consistency of the Supreme Court in upholding justice and legal certainty within the field of intellectual property rights. The research employs a normative (doctrinal) legal method using statutory, conceptual, and case approaches based on the Supreme Court Decision No. 1865 K/Pdt.Sus-HKI/2022. The data consist of primary, secondary, and tertiary legal materials, including legislation, academic literature, and relevant jurisprudence. The results show that novelty is an essential requirement for obtaining legal protection over industrial designs, while good faith serves as both a moral and juridical filter to prevent the misuse of rights by unqualified parties. The Supreme Court emphasized that legal protection is granted only if the design is genuinely new, aesthetically valuable, and registered with honesty and legitimate intention. The study concludes that the principles of novelty and good faith hold fundamental importance in Indonesia’s industrial design legal system. Both serve as the core foundation in determining the validity of registration and protection of industrial designs. The study recommends strengthening technical regulations and enhancing substantive examination by the Directorate General of Intellectual Property (DGIP) to ensure that industrial design protection becomes more effective, fair, and responsive to the growth of the creative industry.